2018
DOI: 10.24884/0042-4625-2018-177-2-52-56
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Morphological Aspects of the Application of Platelet Growth Factors in Patients With Pilonidal Cyst With Abscess

Abstract: В в е д е н и е. Одним из самых распространенных заболеваний в колопроктологии является пилонидальная киста, которая встречается у 3-6 % населения с заболеваемостью 26 случаев на 100 000 человек [1]. Как правило, пилонидальная киста наблюдается у молодых мужчин, и в 2-3 раза

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 2 publications
0
6
0
1
Order By: Relevance
“…Five studies investigated the use of PRP in open pilonidal surgery [26–28, 30, 31], three in minimally invasive pilonidal surgery [29, 33, 34], and one study reported patients in both groups [32]. A total of 621 and 309 patients were included in the open and minimally invasive groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Five studies investigated the use of PRP in open pilonidal surgery [26–28, 30, 31], three in minimally invasive pilonidal surgery [29, 33, 34], and one study reported patients in both groups [32]. A total of 621 and 309 patients were included in the open and minimally invasive groups, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 37 studies were identified and nine met the inclusion criteria (Tables 2 & 3); the included studies originated from Greece [26], Iran [27][28][29], Russia [30], Egypt [31] and Turkey [32][33][34] and were conducted between 2009 and 2021. Eight included studies were RCT's [26][27][28][29][30][31][32][33], and one was a case control study by Kurt et al [34], and all studies compared PRP treated wounds to dressings alone (Tables 2, 3). Five studies applied PRP solution to wounds on multiple days post-operatively [26,28,[30][31][32], while the other four studies all applied it within the first 36 h [27,29,33,34].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Однак, епітелізація вторинних норицевих ходів відбувається значно повільніше ніж первинних, оскільки процес розповсюджується з герміногенної зони дна розірваного волосяного фолікула, який має значно більший мітотичний потенціал у порівнянні зі звичайним епітелієм шкіри [13]. Окрім цього, в даному процесі мають значення вроджені чинники будови крижово-куприкової ділянки, такі як: виразність волосяного покрову, індивідуальна морфологічна особливість волосяних стрижнів, наявність мезенхімальної тканини у загальній структурі «причинної» зони можливого ураження, а також функціональна активність потових та сальних залоз, яка залежить від індивідуальної, зазвичай вродженої, гормональної складової, доказом чого є факт переважання ПХ у дітей та осіб молодого віку [1,5].…”
Section: клінічний випадокunclassified